The role of age and business coaching in the relationship of lean startup approach and innovative work behavior of women entrepreneurs during COVID-19 - Na, Cui; Khalid, Rimsha; Raza, Mohsin; Ramirez-Asis, Edwin; Huerta-Soto, Rosario; Jahanger, Atif (Frontiers in Psychology, 2022)
The purpose of the start-up approach is to find an appropriate course of action that adds value to the economy's development. The current study is aimed to determine the effect of the lean start-up approach with mediating effect of business coaching to foster innovative work behavior in women entrepreneurs. Additionally, the study also examines the moderating effect of age on the lean start-up approach and innovative work behavior. A quantitative approach was employed. The findings show that the relationship between the lean start-up approach and innovative work behavior is significant. Moreover, findings also revealed a significant mediating effect of business coaching and moderating effect of age. This research encourages practitioners and scholars to deal with women entrepreneurship incubation initiatives in the lean startup methodology. Furthermore, this study also leads to a deeper understanding of women's ideas for business exploration, growth, and implementation. The study contends that guidelines and directives are critical for creative entrepreneurial behavior.